Peningkatan Metode Pembelajaran Kontekstual untuk Meningkatkan Motivasi Belajar Anak Slow Learner di Sekolah Dasar KELAS 5 SDN 1 Jamblang - Aghisni Aghisni; Faniar Sesara Maharani; Fery Ichsan Nugraha; Wahyu Arif Gunawan; Sati Sati; Dian Setiawati (Journal on Education, 2025)
Slow learners in elementary schools often face challenges in maintaining learning motivation, which has an impact on their academic achievement. This study aims to improve the learning motivation of slow learner students in grade 5 at SDN 1 Jamblang through the application of contextual learning methods. The research method used is classroom action research (CAR) with a cycle model, including planning, implementation, observation, and reflection. Data were collected through observation, interviews, and student learning motivation questionnaires. The results of the study showed that the contextual learning method was able to significantly improve student learning motivation. In the first cycle, student learning motivation increased by 20%, and in the second cycle, the increase reached 35% compared to the initial conditions. Learning that is relevant to students' daily lives, the use of concrete media, and interactive approaches have proven effective in helping slow learner students understand the material and increase their involvement in the learning process. This study emphasizes the importance of implementing contextual learning methods as a strategy to support the learning needs of slow learner students. The results of this study provide practical contributions for teachers in developing inclusive and effective learning approaches in elementary schools.